Optimization of Feedback FET with Asymmetric Source Drain Doping Profile - Inyoung Lee; Hyojin Park; Quan The Nguyen; Garam Kim; Seongjae Cho; Ilhwan Cho (Micromachines, 2022)
A feedback field-effect transistor (FBFET) is a novel device that uses a positive feedback mechanism. FBFET has a high on-/off ratio and is expected to realize ideal switching characteristics through steep changes from off-state to on-state. In this paper, we propose and optimize FBFET devices with asymmetric source/drain doping concentrations. Additionally, we discuss the changes in electrical characteristics across various channel length and channel thickness conditions and compare them with those of FBFET with a symmetric source/drain. This shows that FBFET with an asymmetric source/drain has a higher on-/off ratio than FBFET with a symmetric source/drain.